Jump squats performed with both light and heavy loads have similar effects on the physical performance of elite rugby players during the initial phase of the competitive period - Loturco, I.; Pereira, L. A.; Moura, T. B. M. A.; Mercer, V. P.; Betelli, M. T.; Ramos, M. S.; Zabaloy, S.; Pareja-Blanco, F. (Journal of Human Kinetics, 2024)
We examined the effectiveness of two different jump-squat (JS) loading ranges on the physical performance of rugby players. Twenty-eight elite male rugby players were divided into two JS training groups: a light-load JS group ("LJS"; JS at 40% of the one-repetition maximum [1RM] in the half-squat (HS) exercise) and a heavy-load JS group ("HJS"; JS at 80% HS-1RM). Players completed the distinct training programs over four weeks, three times per week, during the initial phase of the competitive period. Pre- and post-training tests were conducted in the following sequence: vertical jumps, a 30-m speed test, peak power in the JS and the HS, and maximum isometric force in the HS. Additionally, the rating of perceived exertion (RPE) was assessed at the end of all training sessions throughout the intervention. A two-way ANOVA with repeated measures, followed by the Tukey`s post-hoc test, was employed to analyze differences between groups. The level of significance was set at p < 0.05. Effect sizes were used to assess the magnitude of differences between pre- and post-training data. Except for the RPE values (which were lower in the LJS group), no significant changes were detected for any other variable. In summary, using either a light- (40% HS-1RM) or a heavy-load (80% HS-1RM) JS during the initial phase of the competitive period is equally effective in maintaining physical performance levels attained during the preceding training period (pre-season), with the significant advantage of the light-load protocol resulting in lower levels of the RPE. This finding may have important implications for resistance training programming, especially in disciplines where acute and chronic fatigue is always a problematic issue.